2013
DOI: 10.1038/cddis.2013.441
|View full text |Cite
|
Sign up to set email alerts
|

AEBP1 upregulation confers acquired resistance to BRAF (V600E) inhibition in melanoma

Abstract: An activating BRAF (V600E) kinase mutation occurs in approximately half of melanomas. Recent clinical studies have demonstrated that vemurafenib (PLX4032) and dabrafenib, potent and selective inhibitors of mutant v-raf murine sarcoma viral oncogene homolog B1 (BRAF), exhibit remarkable activities in patients with V600 BRAF mutant melanomas. However, acquired drug resistance invariably develops after the initial treatment. Identification of acquired resistance mechanisms may inform the development of new therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 41 publications
4
76
0
Order By: Relevance
“…41,42 In addition, melanomas are exceptionally resistant to chemotherapy treatment and have a high incidence of relapse. [43][44][45][46][47] Our previous 8 and current studies have revealed a prominent role of deregulated guanylate pools in melanoma progression. Altered expression of enzymes involved in guanylates biosynthesis priming the cells toward an increase in guanylates production occurs already in primary melanomas (GMPR) and peaks at the metastatic stage (IMPDH2, GMPR, and GMPS) (Wawrzyniak et al 8 and Figure 3 and Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 56%
“…41,42 In addition, melanomas are exceptionally resistant to chemotherapy treatment and have a high incidence of relapse. [43][44][45][46][47] Our previous 8 and current studies have revealed a prominent role of deregulated guanylate pools in melanoma progression. Altered expression of enzymes involved in guanylates biosynthesis priming the cells toward an increase in guanylates production occurs already in primary melanomas (GMPR) and peaks at the metastatic stage (IMPDH2, GMPR, and GMPS) (Wawrzyniak et al 8 and Figure 3 and Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 56%
“…The mechanisms regulating cell type-dependent involvement of NF-kB remain to be clarified. Regardless, our results indicate that RIP1 is responsible, at least in part, for constitutive NF-kB activation that is commonly found at high levels in melanoma cells (29,40).…”
Section: Discussionmentioning
confidence: 64%
“…NF-kB activity assays were performed using an assay kit (Qiagen) as per the manufacturer's instructions (29). Briefly, cells transfected with the NF-kB activity reporter with or without cotransfection with indicated siRNAs or cDNAs were subjected to Dual-Luciferase Reporter Assay (Promega) after desired treatment.…”
Section: Nf-kb Reporter Assaysmentioning
confidence: 99%
“…While response rates in this sub-population are impressive, approximately half do not respond, and the majority of the responders will eventually acquire resistance [10] . Many genetic mechanisms of resistance have been cataloged [11] , including NF1 loss-of-function mutations [12] , NRAS activating mutations, BRAFV600E splicing variant, MEK1 mutation, COT expression, BRAFV600E amplification, BRAF G469L mutation [13] , concurrent MEK2 mutation and BRAF amplification [14] , AEBP1 upregulation [15] , MAP2K2 and MITF genomic alterations [16] and MEK2 Q60P mutation [17] , all of which result in reactivation of MAPK signaling, as well as the activation of parallel survival pathways such IGF1R/PI3K-AKT signaling [18] .…”
Section: V600 Point Mutations In Melanomamentioning
confidence: 99%